The effects of brokerage houses on capital markets - Pergel, Ülkü Pınar (My University, 2005)
THE EFFECTS OF BROKAGE HOUSES ON THE CAPITAL MARKETS The main goal of this study is to measure brokerage houses' effectiveness via data envelopment analysis by regarding the turnover they performed in ISE and commission incomes they gained as a result of this activity as output for the purpose of examining the effects of brokerage houses on capital markets. When we look at the market structure, it is obvious that brokerage houses attain their major incomes through intermediation activities they perform, though it has been changing gradually. The main inputs utilized by brokerage houses while implementing these activities are capital, number of personnel and operating expenses. In the light of this, the description of brokerage houses' efficiency can be stated as ensuring the maximum trading volume, active accounts and commission income by using minimum owner's equity, personnel and operating expenses. It was determined that most of the brokerage houses didn't operate as per the description of efficiency and had idle capacity owing to insufficient volume according to data envelopment analysis based on the data that belongs to 74 brokerage houses which were active between the years 2000 - 2004. ARACI KURUMLARIN SERMAYE PİYASALARI ÜZERİNE ETKİLERİ Çalışmanın temel amacı aracı kurumların sermaye piyasalarına etkilerini incelemek amacıyla IMKB hisse senetleri piyasasında gerçekleştirdikleri işlem hacmi ve bu faaliyetten elde ettikleri komisyon gelirlerinin çıktı olarak kabul edip veri zarflama analizi yöntemini kullanarak etkilerini ölçmektir. Piyasa yapısına baktığımızda yavaş yavaş değişmeye başlasa da aracı kurumlar temel gelirlerinin yaptıkları aracılık faaliyetlerinden kazandıkları açıktır. Aracı kurumlar bu faaliyetlerinin yerine getirirken kullandıkları temel girdiler ise sermaye, personel sayısı ve genel giderlerdir. Buradan hareketle aracı kurumlar için yapılan etkinlik tanımına minimum özkaynak, personel ve genel yönetim gideri kullanarak en fazla işlem hacmi, bakiyeli hesap sayısı ve komisyon geliri elde etmektir. 2000 - 2004 yılları arasında faaliyet gösteren 74 aracı kurum verileri kullanılarak yapılan veri zarflama analizi sonuçlarına göre birçok aracı kurum etkinlik tanımına uygun faaliyet göstermediği, yetersiz işlem hacimleri nedeniyle atıl kapasiteye sahip oldukları tespit edilmiştir.
Keywords: Sermaye Piyasası; Sermaye Piyasası_Aracı Kurumlar